ANALISIS STUDI KELAYAKAN BISNIS PT INDOMARCO PRISMATAMA POINT COFFEE MENGHADAPI PERSAINGAN INDUSTRI KOPI PERKOTAAN INDONESIA - Dini Vientiany; Nadia; Istiqomah; Nabila Chairunnisa Br. Karo (INTERNATIONAL, Journal of Sharia Business Management, 2025)
The coffee industry in Indonesia has experienced rapid growth in line with changes in lifestyle, particularly among students and young professionals. Coffee shops are no longer merely places to consume beverages but have evolved into spaces for social interaction, studying, and working. This study aims to analyze the feasibility of the Point Coffee business using a business feasibility study approach covering market and marketing aspects, legal aspects, technical and operational aspects, management, financial aspects, sharia and halal compliance, socio-economic aspects, and environmental considerations. The research method employed is descriptive qualitative, with data collected through observation, a mini-survey of potential consumers, and literature review. The results indicate that Point Coffee has strong market potential, primarily targeting students and young professionals, supported by a strategic location, affordable pricing, and a fast-service concept. From a financial perspective, the business is projected to reach its break-even point within 1–2 years with efficient operational management. Furthermore, Point Coffee is considered feasible in terms of legal compliance, management structure, and adherence to sharia and halal principles. The business also generates positive social and economic impacts by creating employment opportunities, utilizing local coffee beans, and implementing environmentally friendly practices. Based on these findings, Point Coffee is deemed feasible to be operated and developed sustainably.